2018
DOI: 10.1039/c7tc05395a
|View full text |Cite
|
Sign up to set email alerts
|

Effective modulation of the photoluminescence properties of 2,1,3-benzothiadiazoles and 2,1,3-benzoselenadiazoles by Pd-catalyzed C–H bond arylations

Abstract: A one step procedure towards the synthesis of 4-aryl-2,1,3-benzothiadiazoles and 4-aryl-2,1,3-benzoselenadiazoles using Pd-catalyzed C–H bond arylations was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 75 publications
1
15
0
Order By: Relevance
“…The compound was synthesized according to the general procedure using 4‐chlorophenylboronic acid (153 mg, 0.98 mmol, 2.1 equiv.). Purification by column chromatography (hexane/CH 2 Cl 2 1 : 1, R f =0.48) gave 7 as a colourless solid (55 mg, 48 %) whose characterization data was in accordance with reported literature [36] . 1 H NMR (400 MHz, CDCl 3 ): δ (ppm)=8.04−8.00 (m, 1H), 7.90−7.87 (m, 2H), 7.71−7.67 (m, 2H), 7.53−7.49 (m, 2H).…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…The compound was synthesized according to the general procedure using 4‐chlorophenylboronic acid (153 mg, 0.98 mmol, 2.1 equiv.). Purification by column chromatography (hexane/CH 2 Cl 2 1 : 1, R f =0.48) gave 7 as a colourless solid (55 mg, 48 %) whose characterization data was in accordance with reported literature [36] . 1 H NMR (400 MHz, CDCl 3 ): δ (ppm)=8.04−8.00 (m, 1H), 7.90−7.87 (m, 2H), 7.71−7.67 (m, 2H), 7.53−7.49 (m, 2H).…”
Section: Methodssupporting
confidence: 87%
“…Purification by column chromatography (hexane/CH 2 Cl 2 85 : 15, R f = 0.30) gave 11 as a white solid (57 mg, 48 %) whose characterization data was in accordance with reported literature. [36] 1 H NMR (400 MHz, CDCl 3 ): δ (ppm) = 8.41À 8.38 (m, 2H), 8.16À 8.12 (m, 2H), 8.11 (dd, J = 8.5, 1.3 Hz, 1H), 7.79 (dd, J = 7.0, 1.3 Hz, 1H), 7.74 (dd, J = 8.5, 7.0 Hz, 1H). 13 C NMR (101 MHz, CDCl 3 ): δ (ppm) = 155.…”
Section: -(4-nitrophenyl)-213-benzothiadiazole (11)mentioning
confidence: 99%
“…The method proved efficient for a variety of electron-donating and electron-accepting aryl halide substrates and good-to-excellent yields are generally obtained. It should be noted that, under the conditions shown in Scheme 1 , C–H activation on the BT alone resulted in multiple arylation at the 5 and 6 positions in addition to the targeted 4 and 7 positions; however, Doucet and co-workers recently reported a phosphine-ligand free mono- and dual C–H activation of 2,1,3-benzothiadiazole in DMA solvent with high-to-moderate yields [ 22 ]. Unwanted over-arylation of the products was also seen when coupling the acceptors with 2-bromothiophenes having hydrogen in the 5-positions, which was addressed by the use of 2-bromo-5-(trimethylsilyl)thiophenes.…”
Section: Direct Arylation Of Electron-poor π-Conjugated Small Molementioning
confidence: 99%
“…2,1,3-benzothia/selenadiazoles are neutral 10 π-electron heteroaromatics which have been actively investigated for the development of organic photovoltaics and organic lightemitting diodes. [1][2][3] Similar to many other chalcogen-nitrogen π-heterocycles, they possess high electron affinity making them effective electron acceptors. [4] For this reason, they represent a pivotal framework for the construction of organic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…[15] In earlier work we have shown that 4-nitrobenzofurazan 1 c [16] is a representative of an another class of neutral electro-philes whose C-electrophilicity can be quantitatively described by the linear free enthalpy relationship (1), [17] where E parameter measures the strength of the electrophile, k is a second-order rate constant, while N and s N characterize the nucleophiles reactivity. log k ð20 � CÞ ¼ s N ðE þ NÞ (1) In an effort to obtain a quantitative measure of the reactivity of nitro derivatives of 2,1,3-benzothiadiazole and 2,1,3-benzoselenadiazole towards nucleophilic addition processes, [18][19][20][21][22][23][24] we now report on the kinetic and structural analysis of the coupling reaction of 4-nitrobenzothiadiazole 1 a and 4-nitrobenzoselenadiazole 1 b with the reference nitroalkyl anions 2 a-c (Scheme 1, Table 1) in order to evaluate the electrophilic parameter E at the C-7 position of the two electrophiles 1 a and 1 b according to Eq. (1) and to include them into the comprehensive electrophilicity scale of Mayr.…”
Section: Introductionmentioning
confidence: 99%